Brain abscess caused by Nocardia farcinica in a person living with HIV - Lele Yu; Jun Yan; Zhongdong Zhang; Feng Li; Rongrong Zheng; Jinchuan Shi (BMC Infectious Diseases, 2024)
Abstract Nocardia farcinica is the most pathogenic Nocardia, which is easy to disseminate. It can be caused by trauma, and even lead to severe lung or central nervous system infection. This report covers a case of Nocardia brain abscess in an HIV patient, who underwent resection of the brain abscess, followed by anti-infective therapy with sulfamethoxazole and meropenem, and eventually made a good recovery. The mortality rate of Nocardia farcinica brain abscess has been attributed to the severity of the underlying disease, the difficulty in identifying the pathogen, and its inherent resistance to antibiotics, leading to inappropriate or late initiation of treatment. Medication should follow the principle of sufficient dosage and sufficient course of treatment.